"Crystallized Metastable Operations in Disfiguring Figurations [catalogue text on an artwork by the artist Kirstin Burckhardt]" - Henderson, Marius (Fraud, Fake and Fame, 2016)
Keywords: Catalogue Essay; Drawing; Conceptual Art; Affect Theory

"Editorial" - von Gleich, Paula; Henderson, Marius; Humburg, Jasmin; Lange, Julia; Nikolova, Mariya Dimitrova; Spatzek, Samira (COPAS : Current Objectives of Postgraduate American Studies, 2017)

Entangled Memories: Remembering the Holocaust in a Global Age - Henderson, Marius; Lange, Julia (Universitätsverlag Winter, 2017)
Keywords: Cultural Studies; Representations of the Shoah; Holocaust Studies; Transnational American Studies

"'Here is the trash heap, nothing there except a muted wailing': Dithering in Negativity and the Failure to Move on" - Henderson, Marius (The Failed Individual: Amid Exclusion, Resistance, and the Pleasure of Non-Conformity, 2017)
Keywords: Black Diasporic Theory; Experimental Poetry; Black Metal Theory; Queer Theory

"How to Perform Entangled Memories: On Seeing in Not-Seeing" - Henderson, Marius; Seehusen, Jana (2017)
Keywords: Cultural Studies; Aesthetic Theory; Film Studies; Representations of the Shoah; Holocaust Studies

"Introduction" - Henderson, Marius; et al. (Entangled Memories: Remembering the Holocaust in a Global Age, 2017)
Keywords: Cultural Studies; Representations of the Shoah; Holocaust Studies; Transnational American Studies

Introduction - Paul, Heike; Marak, Sarah; Gerund, Katharina; Henderson, Marius (Lexicon of Global Melodrama, 2022)

Laurence Anyways (2012) - Henderson, Marius; Sawallisch, Nele (2022)
CRIS-Team Scopus Importer:2024-12-16

Lexicon of Global Melodrama - Paul, Heike; Marak, Sarah; Gerund, Katharina; Henderson, Marius (Transcript-Verlag, 2022)
This new go-to reference book for global melodrama assembles contributions by experts from a wide range of disciplines, including cultural studies, film and media studies, gender and queer studies, political science, and postcolonial studies. The melodramas covered in this volume range from early 20th century silent movies to contemporary films, from independent arthouse productions to Hollywood blockbusters. The comprehensive overview of global melodramatic film in the Lexicon constitutes a valuable resource for scholars and practitioners of film, teachers, film critics, and anyone who is interested in the past and present of melodramatic film on a global scale. The Lexicon of Global Melodrama includes essays on All That Heaven Allows, Bombay, Casablanca, Die Büchse der Pandora, In the Mood for Love, Nosotros los Pobres, Terra Sonâmbula, and Tokyo Story.
CRIS-Team Scopus Importer:2024-12-16

"Luftmenschen, Golems, and Jewish Punks: On the Pop-Cultural Reflection of Jewish Identity in the Post-Shoah" - Henderson, Marius; Engelmann, Jonas (2017)
Keywords: Cultural Studies; Representations of the Shoah; Holocaust Studies; Transnational American Studies

Melancholia (2011) - Henderson, Marius (2022)
CRIS-Team Scopus Importer:2024-12-16

Notes on the Alluring Weirdness of (Materialist) Rumination and Regurgitation: Reading Ariana Reines and Jamie Stewart - Henderson, Marius (Spaces and Fictions of the Weird and the Fantastic, 2019)
Marius Henderson’s chapter discusses rumination and regurgitation as modes of the figurative and literal, conceptual and embodied reprocessing of materials, which works with, through, and occasionally against plain juxtaposition. Taking Ariana Reines’s poetry collection The Cow (2006) as well as specific aspects of the sonic and lyrical works of Jamie Stewart/Xiu Xiu as touchstones, this chapter scrutinizes connections between weird politico-aesthetic practices of rumination and regurgitation and contemporary materialist theories. Via material-semiotic figurations—such as “the cow,” as an index of feminized ruminating guts in Reines’s poetry or the evocation of “self-abolition” in Stewart’s works—the artistic practices of Reines and Stewart reprocess the weirdness of their form and render palpable the violent structural formations that undergird it.
CRIS-Team Scopus Importer:2024-12-16

"Soft Berry Metal: Eine 'häretische' Annäherung an Black Metal Theory" - Henderson, Marius (testcard #23: Transzendenz – Ausweg, Fluchtweg, Holzweg?, 2013)

"Tentative Heretical Notes on Queer ‘Necro’ Practices and Sensibilities" - Henderson, Marius (Proceedings from the Summer School for Sexualities, Cultures and Politics 2014, 2015)
Keywords: Black Metal Theory; Queer Theory

The public mind and the politics of postmillennial U.S.-American writing - Mathieson, Jolene; Henderson, Marius; Lange, Julia (De Gruyter, 2022)
The first chapter of The Public Mind and the Politics of Postmillennial U.S.-American Writing initially traces and recounts some of the major developments to have taken place in U.S.-American fiction in the last twenty years. Traditional, 20th-century modes of realism and postmodernism have since been succeeded by writerly practices that, in one way or another, are relatable to neorealism, whether it be via outright affirmation or critical experimentation and appropriation. The re-emergence of investments in notions formerly combatted by postmodernists, such as embodied "authenticity," is accompanied by an ongoing awareness toward complexity and the fundamental entanglement of writers, critics, and the reading public with pressing political concerns, and at times oppressive, social and economic discursive and structural formations. The introduction provides an overview of all three sections of this volume's collection of essays as well as of each its fourteen chapters. All contributions share said awareness toward the seemingly inextricable intertwinement of postmillennial U.S.-American writing with the reading public as well as the extratextual contexts in which it is embedded, whether this writing be novelistic or more experimental.
CRIS-Team Scopus Importer:2022-10-07

"Verharrend in Nicht-Bewegung" - Henderson, Marius (Bewegungsformen: folgendes, 2016)
Keywords: Affect Theory; Queer Theory; Afro-Pessimism